The face of Tutankhamun - British Broadcasting Corporation; Arts and Entertainment Network ([London] British Broadcasting Corp., 1992)
This four volume documentary traces archaeologist Howard Carter's beginnings in rural England to the Valley of the Kings. It presents the story of Tutankhamun from the moment of Carter's discovery to the current problems modern civilization faces in trying to preserve the treasures for future generations. It also shows how the excavation made Tutankhamun a pivotal cultural icon of the twentieth century.
[v. 1.] The great adventure -- [v. 2.] Wonderful things -- [v. 3.] The Pharaoh awakes -- [v. 4.] Heads in the sand.
Videocassette release of the 1992 television program.
Title on container: King Tut : the face of Tutankhamun.
Executive producers, Roy Davies [and] Jeremy Bennett ; producers, Derek Towers and David Wallace ; presented and written by Christopher Frayling ; hosted by Jack Perkins.
Keywords: Tutankhamen, King of Egypt; Tutankhamen, King of Egypt -- Tomb; Carter, Howard -- 1873-1939.; Excavations (Archaeology) -- Egypt; Egypt -- Antiquities